Shear Wave Velocity results of non-alcoholic fatty liver disease in diabetic patients - Yılmaz, Birnur; Şener, Özgür Kürşat; Çevik, Halime (Journal of Surgery and Medicine, 2019)
Aim: To evaluate liver stiffness degree in non-alcoholic fatty liver disease with type II diabetes mellitus patients via Shear Wave Elastography (SWV) measurement. SWV elastography values were compared to degree of hepatic steatosis, liver aminotransferases, lipid profile and body-mass index. Methods: In this case-control study, 110 patients with non-alcoholic fatty liver disease, followed by a general internal medicine out patient clinic (57 male 53 female mean age 50.17) and a control group of 50 healthy adults (26 males 24 females mean age 48.26) without liver disease and sonographically grade 0 steatosis were admitted to the study. Right lobe of the liver parenchyma in each person was evaluated for a total of ten measurements. Sonographic grade of the hepatic steatosis in patients, SWV values and laboratory values simultaneously received were compared. Results: SWV average speed value is calculated to be 2.26 ± 0.57 m/s in patient group; 1.71± 0.34 m/s in the control group; 2.15 ± 0.63 m/s in patients with grade I steatosis; 2.25 ± 0.42 m/s in patients with grade II steatosis, 2.72 ± 0.43 m/s in patients with grade III steatosis. SWV values indicate a statistically significant difference in patient and control groups (p < 0.01). There wasn’t a statistically significant difference of liver SWV values among the three grades of steatosis. Conclusion: Acoustic radiation force impulse can be used to detect of decreased stiffness in liver (on average 2 and over SWV values) with increase of triglycerides, aspartate aminotransferase and alanin aminotransferaz in patients.